Socially Responsible Investing and Sustainable Indices: A Sustainability Agenda. Issue 2 (December 2021) - M. R., Firdaus Khan
COVID-19 pandemic has brought climate change and socially responsible investing back to the forefront. Sustainable investing, though well-entrenched in developed countries, is slowly gaining traction in emerging markets. Sustainability indices operate as quality indicators and bridge information gap. This study explores the usefulness of three such indices and offers an autoregressive moving average model on Carbonex series for sustainable investments on Bombay Stock Exchange. However, the model fails to align with the long-term goals of socially responsible investing and the investor community needs to engage with regulators, corporations and rating agencies so that these sustainability indices can better serve their information needs and offer a valid measure of sustainable practices. COVID-19 brings with it the opportunity to ideate and envision innovative approaches to support a carbon-free economic agenda and to design eco-friendly infrastructure, planned urban development and transition to clean energy. Take–make–consume–waste attitude is out and the philosophy of preserve–endure–nurture–bequeath will be the new normal.